2015
DOI: 10.14198/jhse.2015.10.proc1.33
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate response to game load of U19 female basketball players

Abstract: Vencúrik, T., Nykodým, J., & Struhár, I. (2015). Heart Rate Response to Game Load of U19 Female Basketball Players. J. Hum. Sport Exerc., 9(Proc1), pp.S410-S417. The aim of the study is to compare the intensity of game load between player positions (guards, forwards, centers) and between the 1 st and the 2 nd half of the basketball games in female category U19. Ten female basketball players (17.6 ± 0.9 years old) participated in this study. The beep test was used to determine the maximal heart rate (HRmax) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…the traditional definition of minutes played). This review identified a wide range of methods used to determine training duration in basketball, and a significant number of studies (n = 24) that failed to report how duration was defined and calculated [32,49,52,66,69,71,72,75,84,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. A commonly used description of duration methodology in basketball was defined in 1995 by McInnes et al [47], where total time was calculated as "all of the time that the subject was on the court, including all stoppages in play such as time-outs, free-throws and out-of-bounds, but excluding breaks between quarters, or time that the subject was substituted out of the game" [47].…”
Section: Methodology For Quantifying Durationmentioning
confidence: 99%
“…the traditional definition of minutes played). This review identified a wide range of methods used to determine training duration in basketball, and a significant number of studies (n = 24) that failed to report how duration was defined and calculated [32,49,52,66,69,71,72,75,84,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106]. A commonly used description of duration methodology in basketball was defined in 1995 by McInnes et al [47], where total time was calculated as "all of the time that the subject was on the court, including all stoppages in play such as time-outs, free-throws and out-of-bounds, but excluding breaks between quarters, or time that the subject was substituted out of the game" [47].…”
Section: Methodology For Quantifying Durationmentioning
confidence: 99%
“…A similar decline had been reported in other studies. 30,46 The lack of significant difference between the two halves of the game for forwards is however supported by Vencurik et al 51 who witnessed no changes between certain positions physiological demands across the two halves of a female basketball match.…”
Section: Heart Rate Intensitiesmentioning
confidence: 97%